DNA methylation imprinting errors in spermatogenic cells from maturation arrest azoospermic patients. (10th March 2017) - Marques, P. I.; Fernandes, S.; Carvalho, F.; Barros, A.; Sousa, M.; Marques, C. J.
Summary: Imprinting errors have been described in spermatozoa from infertile patients with oligozoospermia and azoospermia. However, little is known about methylation of imprinted genes in other spermatogenic cells from azoospermic patients. Therefore, we aimed to evaluate the methylation status of single CpGs located in the differentially methylated regions (DMRs) of two imprinted genes, one paternally ( H19 ) and one maternally ( MEST ) methylated, in primary spermatocytes of azoospermic patients presenting complete (MAc, n = 7) and incomplete (MAi, n = 8) maturation arrest, as well as in other spermatogenic cells from MAi patients that presented focus of complete spermatogenesis in some seminiferous tubules. We observed H19 imprinting errors in primary spermatocytes from one MAi patient and MEST imprinting errors in one MAi and two MAc patients. Additionally, H19 imprinting errors were observed in elongated spermatids/spermatozoa from one MAi patient. Nevertheless, no statistical differences were found for H19 and MEST global methylation levels (percentage of methylated and unmethylated CpGs, respectively) between patients with complete and incomplete MA and also between MA groups and a control group. These results provide further evidence that imprinting errors occur in spermatogenic cells from patients presenting impaired spermatogenesis, as we and others have previously described in ejaculated and testicular spermatozoa. As paternal imprinting errors can be transmitted to the embryo by the sperm cell, they can provide a possible explanation for poor embryo development and/or low pregnancy rates as correct expression of imprinted genes is crucial for embryo and placental development and function. Therefore, in cases with male factor infertility where unsuccessful in vitro fertilization (IVF) treatments are recurrent, analysis of imprinting marks in spermatozoa might be a useful diagnostic tool.